Engineering Mycobacteriophage Bxb1 integrase for improved integration efficiency of target gene in mammalian cells - Ali, Abeer (My University, 2025)
Mammalian cell display represents a critical platform in therapeutic antibody discovery, dependent on the stable genomic integration and expression of target genes within host cells. For this purpose, serine integrases, particularly mycobacteriophage Bxb1 integrase, is commonly used due to its site-specificity and efficiency, though wild-type variant may still show limitations in performance. To enhance Bxb1 integrase function, four variant libraries were constructed by targeting residues near its active site. These libraries were assembled using HiFi cloning and introduced into E. coli via an expression vector. Screening was performed by co-transforming cells with a targeting vector and applying a time sensitive, PCR-based selection strategy. Variants showing faster recombination were isolated, sequenced, and functionally assessed. One Bxb1 variant consistently demonstrated improved activity, with 1.68-fold increase in recombination efficiency compared to the wild-type. Computational modeling and preliminary vector copy number analysis support the structural plausibility of the observed improvement. These findings indicate that targeted mutagenesis of Bxb1 integrase enhanced its performance, highlighting the need for further validation in mammalian systems.
Keywords: Bxb1 integrase, co-transformation, HiFi cloning, mammalian cell display, computational analysis, BioLuminate